2019
DOI: 10.1177/1060028019833696
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide Added to a Proton Pump Inhibitor Versus a Proton Pump Inhibitor Alone in Nonvariceal Upper-Gastrointestinal Bleeds

Abstract: Background: Literature indicating clinically relevant benefits of an adjunctive somatostatin analog to standard therapies in nonvariceal upper-gastrointestinal bleeding (NVUGIB) is lacking. Objective: The primary objective of this study was to find the association between outcomes in patients with NVUGIB treated with octreotide and a proton pump inhibitor (PPI; combination group) compared with those treated with a PPI alone. Methods: We conducted a retrospective cohort study of adults admitted within a 5-hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, they are not recommended in NVUGIH (e. g., peptic ulcer bleeding), either before endoscopy or as an adjunctive therapy following endoscopy, since published data show little or no benefit. A recently published retrospective cohort study including 180 patients with acute NVUGIH continues to show no significant differences in outcomes between patients receiving combination therapy (PPI plus octreotide infusion) and those receiving PPI alone (hospital and intensive care unit [ICU] median length of stay, respectively, 6.1 vs. 4.9 days, P = 0.25, and 2.3 vs. 1.9 days, P = 0.24; rebleeding 9 % vs. 12 %, P = 0.63; RBC units transfused 3 vs. 2 units, P = 0.43; and mortality 6.7 % vs. 5.6 %, P = 1.00) [72].…”
Section: Somatostatin and Somatostatin Analoguesmentioning
confidence: 95%
“…However, they are not recommended in NVUGIH (e. g., peptic ulcer bleeding), either before endoscopy or as an adjunctive therapy following endoscopy, since published data show little or no benefit. A recently published retrospective cohort study including 180 patients with acute NVUGIH continues to show no significant differences in outcomes between patients receiving combination therapy (PPI plus octreotide infusion) and those receiving PPI alone (hospital and intensive care unit [ICU] median length of stay, respectively, 6.1 vs. 4.9 days, P = 0.25, and 2.3 vs. 1.9 days, P = 0.24; rebleeding 9 % vs. 12 %, P = 0.63; RBC units transfused 3 vs. 2 units, P = 0.43; and mortality 6.7 % vs. 5.6 %, P = 1.00) [72].…”
Section: Somatostatin and Somatostatin Analoguesmentioning
confidence: 95%
“…Octreotide use is standard of care for variceal bleeding. It is not recommended for routine use in nonvariceal bleeding (8) due to lack of improvement in length of hospitalization and rebleeding in adults (22)(23)(24). There are only a few studies observing effect of octreotide in nonvariceal bleeding in children (25).…”
Section: Discussionmentioning
confidence: 99%
“…The success of endoscopic treatment in patients with UGIB is largely dependent on the skill of the endoscopist. [ 12 ] Although PPIs are now part of standard care, a recent study showed that the bolus and infusion of these drugs, even in high doses, might not be adequate for maintaining a stomach pH ≥6. [ 6 ] Thus, there is a search for adjuvant therapeutic methods that could work with endoscopic treatment and PPIs to improve the outcome in high-risk patients with UGIB.…”
Section: Discussionmentioning
confidence: 99%
“…However, while both drugs are used in the standard care of patients with variceal UGIB, clinical trials have reported contradictory results about their efficacy in patients with NVUGIB. [ 21 22 ]…”
Section: Discussionmentioning
confidence: 99%